Can fish lifts aid upstream dispersal of the invasive red swamp crayfish (Procambarus clarkii) past high‐head hydropower plants?. (1st September 2021) - Santos, José Maria; Amaral, Susana Dias; Pádua, João
Abstract: Many types of fish passage facilities have been built worldwide to mitigate river fragmentation by instream barriers and partially restore upstream movements of fish. Among these, fish lifts are a design that enables fish to pass through high‐head obstacles (>15 m height) and can be considered the most cost‐effective fishway. However, fishways may also be used by non‐native invasive species to disperse and impact new areas and organisms upstream. As far as the authors are aware, this short communication is the first record of the red swamp crayfish ( Procambarus clarkii ) passing through a fish lift. The lift, built at the Touvedo hydropower plant on the Lima River (northwestern Portugal), was mainly designed for the upstream passage of diadromous fish. Fish‐lift use and upstream passage of two crayfish occurred over 3 years (November 2017–October 2020) during periods of turbine shutdown and high water temperatures (18°C). In the present case, the crayfish passage should not pose a serious threat due to the limiting characteristics of the upstream lotic environment. Nevertheless, despite the small sample size, this study shows the importance of considering the passage of invasive crayfish species while planning future fishways and the need to continuously monitor such facilities to detect the passage of this and other non‐native invasive species.